A key to Russian and Eastern European species of Blaps Fabricius, 1775 (Coleoptera: Tenebrionidae: Blaptinae) with the description of a new species from the North Caucasus supported by morphological and molecular data - Nabozhenko, Maxim V.; Chigray, Ivan A.; Ntatsopoulos, Konstantinos; Papadopoulou, Anna (Zootaxa, 2022)
A new species is described from the Central part of the North Caucasus (Russia): Blaps caucasica M. Nabozhenko et I. Chigray sp. n. This taxon was interpreted earlier as B. scabriuscula subalpina Ménétriés, 1832, but both our morphological and molecular genetic analyses showed that it is in fact a separate new species. The following new synonymies are proposed: Blaps verrucosa Adams, 1817 = Blaps scabriuscula Ménétriés, 1832 syn. n., = Blaps montana Motschulsky, 1839 syn. n.; Blaps lethifera Marsham, 1802 = Blaps pterotapha Ménétriés, 1832 syn. n. The rank of one species is reinstated: Blaps subalpina Ménétriés, 1832 stat. resurr. The name Blaps sinuatocollis Solier, 1848 was unambiguously proposed for an infrasubspecific entity and must be excluded from zoological nomenclature. A phylogenetic hypothesis was reconstructed using mitochondrial Cytochrome c oxidase subunit I (COI) sequences for some closely related taxa from the North Caucasus and Ciscaucasia: B. caucasica sp. n., B. lethifera, B. subalpina and B. verrucosa. The resulting tree supports the assignment of two specimens from the Lower Don area (Rostov Region of Russia), earlier interpreted as B. scabriuscula subalpina, to B. lethifera. All known Blaps from Russia and Eastern Europe (countries of the former USSR) are illustrated, and keys on males and females are provided. The status of an invasive species Blaps aff. oblonga Kraatz, 1883 from South Siberia is discussed.